European Regions: Perspectives, Trends and Developments in the 21st Century - Donat, Elisabeth; Meyer, Sarah; Abels, Gabriele (transcript, 2020)
At the beginning of the 21st century, the EU is facing deep political, social, and economic changes. The benefit of supranational organization is no longer obvious to European citizens and questions of legitimacy have accompanied the EU's development over the last decades. Regions – albeit often deemed »obsolete« – present themselves as stable and reliable partners in this turbulent environment: in being important objects of identification to their citizens, but also relevant political and legal entities in the EU's multilevel governance system. This edited volume asks about the role of regions and regional identity in a European Union that is perhaps struggling more than ever about its future.